The Ukraine Support Tracker: Which countries help Ukraine and how? - Arianna Antezza; André Frank; Pascal Frank; Lukas Franz; Ivan Kharitonov; Bharath Kumar; Ekaterina Rebinskaya; Christoph Trebesch (Kiel Institute for the World Economy (IfW Kiel), 2022)
This paper presents the 'Ukraine Support Tracker', which lists and quantifies military, financial and humanitarian aid to Ukraine in the context of the Russia-Ukraine war. This sixth version covers government commitments made between January 24 and August 3, 2022 and has a new detailed overview on weapon deliveries. We track support by 40 governments, including all G7 and European Union member countries, plus by EU institutions (thus including 41 donors). Private donations and aid through non-governmental organizations are not included due to a lack of systematic data, but we do show estimates on government costs of hosting Ukrainian refugees. To value in-kind support like military equipment or foodstuff, we rely on government statements as well as own calculations using market prices. We find significant differences in the scale of support across countries, both in absolute terms and as percent of donor country GDP. In billions of Euros, by far the largest bilateral supporter of Ukraine is the United States, followed by the EU institutions and the United Kingdom. In percent of donor GDP, Eastern European countries stand out as particularly generous, and this is even more so once we account for refugee costs. In the past months (June and July), new commitments have fallen notably, thus further widening the gap between what Ukraine demands and the foreign aid it receives.
Additional information: This is version 5 of the paper based on the 6th release of the database (covering data since January 24 and through August 3, 2022).; More recent version: http://hdl.handle.net/10419/268864
Keywords: F35; F51; H56; H63; H84; H81; 330; International aid; military aid; war; geoeconomics